Antioxidant Effect of Ocimum basilicum Essential Oil and Its Effect on Cooking Qualities of Supplemented Chicken Nuggets - Hafiz Rehan Nadeem; Saeed Akhtar; Tariq Ismail; Muhammad Qamar; Piero Sestili; Wisha Saeed; Muhammad Azeem; Tuba Esatbeyoglu (MDPI AG, 2022)
A commonly observed chicken meat issue is its lipid oxidation that leads to deterioration of its organoleptic and nutritional properties and its further-processed products. Basil (Ocimum basilicum L.) is one of the traditional culinary herbs exhibiting food preservation properties. The current study investigated the essential oil composition, antioxidant activity and in vitro cytotoxic capacity of the essential oil of basil indigenous to Pakistan. GC-MS analysis of the essential oil revealed the presence of 59 compounds that constituted 98.6% of the essential oil. O. basilicum essential oil (OB-EO) exhibited excellent antioxidant activity, i.e., IC50 5.92 ± 0.15 µg/mL as assayed by the DPPH assay, 23.4 ± 0.02 µmoL Fe/g by FRAP, and 14.6 ± 0.59% inhibition by H2O2. The brine shrimp lethality assay identified an average mortality of ~18% with OB-EO at 10-1000 µg/mL, while that of the same concentration range of the standard drug (etoposide) was 72%. OB-EO was found to be non-toxic to HeLa and PC-3 cell lines. TBARS contents were significantly decreased with increase of OB-EO in chicken nuggets. The lowest TBARS contents were recorded in nuggets supplemented with 0.3% OB-EO, whereas the highest overall acceptability score was marked to the treatments carrying 0.2% OB-EO. The results suggest OB-EO as a promising carrier of bioactive compounds with a broad range of food preservation properties, and which has a sensory acceptability threshold level for chicken nuggets falling between 0.2-0.3% supplementation. Future research must investigate the antibacterial impact of OB-EO on meat products preserved with natural rather than synthetic preservatives.